Pengaruh Kualitas Pelayanan dan Nilai Pelanggan terhadap Kepuasan Pelanggan (Studi Kasus pada Penumpang Bus PO. Haryanto Kudus) - Putri Andhansari; Nawazirul Lubis; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Many companies operated on business transport services especially bus caused consequence as fiercely competition in order to get customer and maintain customer satisfaction. Based on those the problem in this research is decrease volume of passenger on PO. Haryanto in 2009-2011. This research aim to know is there any influence between quality services and customer value toward customer satisfaction. Research type is explanatory research. Because of indefinite population so retrieved the sample as much as 100 respondents with Purposive sampling method. The collection of data used questionnaire. Data analysis used linear regression analysis. The result of this research shown that quality services and customer value has positive influence and significant to purchase decision even partially (with the result each 59,9% and 47,9%) and simultaneously 60,2% with quality services as the biggest influence. Advice to PO. Haryanto Kudus to notice some factors such as price determination, besides cost elements also price that set by competitors. Management considered to more disciplining and give referrals especially for some new employee that often become complaint from the customer to always be friendly and more quickly as well as customer demand so can give maximum services to all customer